Life cycle modelling for tourism areas - Alvares, Daniela (2005)
Modelling tourism development cycles associated with planning and investment cycles intends to be a contribution to the understanding of the tourism activity within a continuum process. It allows a better apprehension of the sequence of interdependencies that exist and can be addressed enlarging the well-known concept of tourism product and its life cycle. The proposed model can contribute for monitoring the tourism activity and improve its development in a sustainable way. If the tourist sites use this tool they have more probability to have success, because when the tourism life cycle is monitored it is possible to introduce some corrections upon the inadequate trend. The use of the appropriate indicators to measure the activity is essential to the success of the proposed life cycle modelling, such as can be observed in Madeira Region case study.